1983
DOI: 10.1007/bf00275939
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy and arterial hypertension

Abstract: The relationship between arterial blood pressure and diabetic nephropathy was examined in 61 Type 1 (insulin-dependent) diabetic patients (22 females and 39 males). All patients fulfilled the following criteria: persistent proteinuria (greater than 0.5 g/day), onset of diabetes before 31 years of age, age less than 42 years, serum creatinine less than 130 mumol/l, and no antihypertensive treatment. Thirty Type 1 diabetic patients without persistent proteinuria but matched for sex, age, ideal body weight and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(50 citation statements)
references
References 13 publications
4
45
0
1
Order By: Relevance
“…17 We also noted a high frequency of significantly elevated blood pressure in persons with juvenile-onset type I diabetes at the time of diagnosis of diabetic nephropathy when the serum creatinine was still normal. This confirms the findings of Parving et al , 10 who found a similar blood pressure of 146/96 mm Hg in type I diabetic patients with persistent proteinuria and normal serum creatinine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…17 We also noted a high frequency of significantly elevated blood pressure in persons with juvenile-onset type I diabetes at the time of diagnosis of diabetic nephropathy when the serum creatinine was still normal. This confirms the findings of Parving et al , 10 who found a similar blood pressure of 146/96 mm Hg in type I diabetic patients with persistent proteinuria and normal serum creatinine.…”
Section: Discussionsupporting
confidence: 92%
“…6 " 9 Generally, hypertension has been acknowledged to be a late symptom of diabetic nephropathy, but it was recently demonstrated that elevated blood pressure is also present in patients during early stages of nephropathy, that is, normal level of serum creatinine. 10 It has also been shown that elevated arterial blood pressure has an enormous impact on the progression of diabetic nephropathy.…”
mentioning
confidence: 99%
“…However, recent data suggest that mild or subclinical hypertension may play an important role in accelerating the progression to renal failure in patients with diabetes. Blood pressure is frequently elevated in IDDM patients with proteinuria before the appearance of clinically overt deterioration in renal function (26,27). Even in patients with microalbuminuria, blood pressure is related to the degree of urinary protein excretion (28).…”
Section: Natural History and Complicationsmentioning
confidence: 99%
“…Em um estudo epidemiológico multicêntrico realizado com indivíduos não diabéticos (38), foi evidenciado que os pacientes com microalbu - Não houve diferença significativa, em nosso estudo, em relação aos níveis tanto da PAS como da PAD. São muitos os dados na literatura em relação à associação da PA sistêmica e microalbuminúria e, apesar de um grande número de estudos ter demonstrado essa associação, principalmente com a PAS (13,22,28,(39)(40)(41)(42), outros estudos não observaram este fato, sugerindo que técnicas mais elaboradas e exatas para aferição da pressão arterial, como a monitorização ambulatorial da pressão arterial, talvez se façam necessárias para melhor acurácia no diagnóstico da hipertensão no paciente diabético (28,43).…”
Section: Microalbuminúria Em Pacientes Com Dm1unclassified